Molecular cloning and sequence analysis of the gene of the molybdenum‐containing aldehyde oxido‐reductase of Desulfovibrio gigas The deduced amino acid sequence shows similarity to xanthine dehydrogenase - Thoenes, Ulrich (2019)
In this report, we describe the isolation of a 4020‐bp genomic PstI fragment of Desulfovibrio gigas harboring the aldehyde oxido‐reductase gene. The aldehyde oxido‐reductase gene spans 2718 bp of genomic DNA and codes for a protein with 906 residues. The protein sequence shows an average 52% (± 1.5%) similarity to xanthine dehydrogenase from different organisms. The codon usage of the aldehyde oxidoreductase is almost identical to a calculated codon usage of the Desulfovibrio bacteria.